2019
DOI: 10.1007/s10734-019-00452-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in higher education choice: weighing one’s multiple interests in light of available programmes

Abstract: Recent studies have shown that students' interests are decisive in making a substantiated higher education choice, yet do not indicate how students decide which interests they aim to pursue. This study aimed to find the considerations students have when weighing interests and higher education programmes. Thematic analysis was applied to uncover considerations based on semi-structured interviews with 20 Dutch high-school seniors. Students weighed their interests from an interest-to-programme perspective (contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…As a consequence, educators might do well to determine the baseline subject-related interests of their students, in order to judge the necessity of triggering new, situational interest, or the possibility of appealing to existing, individual interests. The same goes for out-of-school interests, which can be important for study choices and hold learning potential (Holmegaard, 2015;Ito et al, 2018;Vulperhorst, van der Rijst, & Akkerman, 2020). For example, research has shown that involving students' personal interests in school can improve homework completion rates, task interest and engagement (e.g., Hinton & Kern, 1999;Reber, Canning, & Harackiewicz, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, educators might do well to determine the baseline subject-related interests of their students, in order to judge the necessity of triggering new, situational interest, or the possibility of appealing to existing, individual interests. The same goes for out-of-school interests, which can be important for study choices and hold learning potential (Holmegaard, 2015;Ito et al, 2018;Vulperhorst, van der Rijst, & Akkerman, 2020). For example, research has shown that involving students' personal interests in school can improve homework completion rates, task interest and engagement (e.g., Hinton & Kern, 1999;Reber, Canning, & Harackiewicz, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent research has shown that also interests outside the school context can be catalysts for meaningful learning processes, with the potential to develop considerable knowledge and skills (Ito et al, 2018;Krapp, 2002;Renninger & Hidi, 2016). Moreover, out-of-school interests can be of equal value to students in making study and career choices, an interest in gaming for example leading a student to consider choosing Computer Science (Erstad & Silseth, 2019;Holmegaard, 2015, Vulperhorst, van der Rijst, & Akkerman, 2020. Recognition of the powerful role of out-of-school interests has also generated educational research on how to involve students' existing interests into education (e.g., Hinton & Kern, 1999;Reber, Canning, & Harackiewicz, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yet youth themselves may have other views about the positions they have or ought to have, with also other than academic and career motives that drive their actions (e.g., more pressing aims related to health, family, or religion). In fact, adolescents we have been following in this and other interest projects all reported to have multiple academic, leisure, and family interests they equally valued in making balanced study and career decisions (e.g., Vulperhorst et al, 2020).…”
Section: How the Object Frames Developing People In Changing Societiesmentioning
confidence: 97%
“…
The choice of the university course to attend and therefore indirectly the professions connected to it, constitutes a complex operation for a student who finishes secondary school (Vulperhorst, 2020). This choice becomes more difficult if we are talking about courses of study that train border professions, as in the case of university courses in the socio-psycho-pedagogical field, assimilated, in the common feeling, to the point of confusing the borders.
…”
mentioning
confidence: 99%